(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: The main objective of this research was to examine the knowledge, attitudes, and behaviors of undergraduate students in Peshawar, Pakistan, who are studying in different universities. Material and method: For data collection, Google Forms questionnaire was administered to a diverse group of undergraduate students in Peshawar, Pakistan. Out of the collected responses, 384 well-completed forms were chosen for further analysis. The questionnaire comprised four sections: demographics, knowledge, attitude, and practices. Results: In a survey of 384 students, it was found that a significant 92.2% of them were aware of epilepsy, either through personal exposure or reading about it. Additionally, 62.5% reported knowing someone with seizure disorders, and 61.2% had witnessed a seizure event. Impressively, a substantial 83.3% correctly identified epilepsy as a neurological condition. When it came to cognitive capabilities, a noteworthy 75.5% believed that individuals with epilepsy retained normal cognitive function. In terms of treatment, 82.8% of the respondents supported medical intervention as the appropriate approach for managing epilepsy. Conclusion: The study’s findings suggest that undergraduate students in Peshawar, Pakistan, possess a moderate level of knowledge about epilepsy, which is less than what was observed in a similar study conducted in Karachi, Pakistan.